Annotated translation of the book Caminantes del Sol by Edna Iturralde. - Gómez Naranjo, Yolanda Denisse (2018)
This annotated translation of “Caminantes del Sol” by Edna Iturralde was designed to meet the needs of 10 to 13 year-oldchildren as well as the geographical environment in which the plot evolves.This is a crafted translation of literary work with special attentionon language, setting, narrative, lexicon and culture. Such items were observed through linguistic and extralinguistic analysis by extracting the mostrelevant excerpts from the text arranged on tables confronting textual and paratextual items of the language. Simultaneously to the translation, there is set of annotations where the authors mention the technique applied and why it was used. On the extalinguistic analysis, a number of culture-specific items were considered. Among them, the ecology of the region, the material culture with ethnic places, ethnic clothing, tool elements as: utensils and weapons. This work also contains references to parallel passages on organization customs and ideas reflected on the language as expressions and slangs; ethnic names that hold uniqueness and cultural semantic meaning.